Structure, infrared detection device, light-emitting device, and method for manufacturing structure

By using a polycrystalline structure containing alkali metal composite fluoride, combined with pressurization and heating processes, the problem of strong hygroscopicity and high melting point materials in the prior art is solved, and a high-efficiency infrared transmission window suitable for gas sensors and flame detection sensors is realized.

CN119522203APending Publication Date: 2025-02-25PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380052809.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-19
Filing Date
2023-07-07
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, alkali metal fluoride has strong hygroscopicity and is difficult to be applied to gas sensors and flame detection sensors, and alkaline earth metal fluorides with high melting point are difficult to produce structures with high infrared transmittance.

Method used

A polycrystal structure containing a composite fluoride containing an alkali metal is used to form a structure with low porosity and high infrared transmittance by pressurization and heating processes.

Benefits of technology

An infrared transmission window suitable for gas sensors and flame detection sensors is realized, and the moisture resistance and infrared transmission of the structure are improved through simple low-temperature process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119522203A_ABST
    Figure CN119522203A_ABST
Patent Text Reader

Abstract

The structure (1) is provided with a base material (10) containing a continuous phase (11) of a polycrystal of a complex fluoride containing an alkali metal, the structure (1) contains 85% by mass or more of an inorganic substance, the structure (1) contains 50% by mass or more of the polycrystal of the complex fluoride, the porosity of the structure (1) is 30% or less, the median value of the pore diameter of the structure (1) is 500 nm or less, and the pore diameter of the structure (1) is 100 nm or less. The structure (1) has a thickness of 10 [mu] m or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a structure, an infrared detection device, a light-emitting device and a method for manufacturing the structure. Background Art

[0002] Until now, infrared transmission windows using inorganic fluoride as a base material have been used for special applications in the fields of academic research, industry, etc., such as window materials for physical and chemical equipment. Patent document 1 discloses a Fourier transform infrared spectrophotometer, which has a measuring cell whose cell window is composed of one selected from the group consisting of CaF2, BaF2, MgF2, LiF and ZnSe, and measures fluorine-based gas in a sample containing corrosive gas.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2019 / 176624 Summary of the invention

[0006] On the other hand, it is known that there are various gas and flame sensing technologies using infrared detection elements and infrared transmission filters. However, the alkali metal fluorides described above have strong hygroscopicity and are not suitable for general uses such as gas sensors and flame detection sensors. In addition, alkaline earth metal fluorides sometimes have melting points as high as 1200 to 1500°C. If a high-level technology that requires a high temperature of at least 1000°C is not used, there is a risk that a structure with high infrared transmittance cannot be manufactured.

[0007] The present invention is made in view of the problems of the prior art. Furthermore, the object of the present invention is to provide a structure suitable for use in infrared transmission windows of gas sensors and flame detection sensors, and an infrared detection device using the same. In addition, the object of the present invention is to provide a method for manufacturing the above-mentioned structure that can be manufactured by a simple low-temperature process.

[0008] In order to solve the above problems, the structure of the first embodiment of the present invention has a base material of a continuous phase of a polycrystal of a composite fluoride, wherein the composite fluoride contains an alkali metal, the structure contains 85% by mass or more of an inorganic substance, the structure contains 50% by mass or more of a polycrystal of a composite fluoride, the porosity of the structure is 30% or less, the median value of the pore diameter of the structure is 500 nm or less, and the thickness of the structure is 10 μm or more.

[0009] An infrared detection device according to a second aspect of the present invention includes a structure.

[0010] A light emitting device according to a third aspect of the present invention includes a structure.

[0011] The method for manufacturing a structure of the fourth embodiment of the present invention includes a step of pressurizing and heating a raw material under a pressure of 10 to 600 MPa and a temperature of 50 to 300° C., the raw material containing at least one of the following two: a first fluoride containing an alkali metal, a second fluoride containing a metal other than an alkali metal, and water; and a composite fluoride containing at least one of a hydroxyl group and a water molecule. The structure contains 85% by mass or more of an inorganic substance, the structure contains 50% by mass or more of a polycrystal of the composite fluoride, the porosity of the structure is 30% or less, the median value of the pore diameter of the structure is 500 nm or less, and the thickness of the structure is 10 μm or more. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 It is a cross-sectional view schematically showing an example of a structure body according to the present embodiment.

[0013] Figure 2 This is an enlarged cross-sectional view schematically showing another example of the structure of this embodiment.

[0014] Figure 3 It is a cross-sectional view schematically showing an example of the infrared detection device according to the present embodiment.

[0015] Figure 4 This is a schematic diagram showing an example of a light-emitting device according to this embodiment.

[0016] Figure 5 This is a SEM image of Na3AlF6 powder obtained during synthesis observed at a magnification of 10,000 times.

[0017] Figure 6 This is a SEM image of the K2NaAlF6 powder obtained during the synthesis observed at a magnification of 10,000 times.

[0018] Figure 7 This is a SEM image of the NaMgF3 powder obtained during synthesis observed at a magnification of 10,000 times.

[0019] Figure 8 This is the XRD pattern of the powder of the test sample of Example 1.

[0020] Fig. 9 This is the XRD pattern of the powder of the test sample of Example 2.

[0021] Fig.10 It is the XRD spectrum of the raw material of Example 3 and the powder of the test sample.

[0022] Fig.11 It is the XRD spectrum of the raw material of Example 4 and the powder of the test sample.

[0023] Fig.12 It is the XRD spectrum of the raw material of Example 5 and the powder of the test sample.

[0024] Fig.13 This is a secondary electron image obtained by observing the CP-processed (cross-section polished) cross section of the test sample of Example 1 at a magnification of 10,000 times.

[0025] Fig.14 This is a reflected electron image obtained by observing the CP-processed cross section of the test sample of Example 1 at a magnification of 10,000 times.

[0026] Fig.15 This is a secondary electron image obtained by observing the CP-processed cross section of the test sample of Example 2 at a magnification of 10,000 times.

[0027] Fig.16 This is a reflected electron image obtained by observing the CP-processed cross section of the test sample of Example 2 at a magnification of 10,000 times.

[0028] Fig.17 This is a secondary electron image obtained by observing the CP-processed cross section of the test sample of Example 3 at a magnification of 10,000 times.

[0029] Fig.18 This is a reflected electron image obtained by observing the CP-processed cross section of the test sample of Example 3 at a magnification of 10,000 times.

[0030] Fig.19 This is a secondary electron image obtained by observing the CP-processed cross section of the test sample of Example 4 at a magnification of 10,000 times.

[0031] Fig. 20 This is a reflected electron image obtained by observing the CP-processed cross section of the test sample of Example 4 at a magnification of 10,000 times.

[0032] Fig.21 This is a secondary electron image obtained by observing the CP-processed cross section of the test sample of Example 5 at a magnification of 10,000 times.

[0033] Fig. 22 This is a reflected electron image obtained by observing the CP-processed cross section of the test sample of Example 5 at a magnification of 10,000 times.

[0034] Fig.23 This is a secondary electron image obtained by observing the CP-processed cross section of the test sample of Example 1 at a magnification of 2000 times.

[0035] Fig.24 This is a reflected electron image obtained by observing the CP-processed cross section of the test sample of Example 1 at a magnification of 2000 times.

[0036] Fig.25 This is a secondary electron image obtained by observing the CP-processed cross section of the test sample of Comparative Example 1 at a magnification of 2000 times.

[0037] Fig.26 This is a reflected electron image obtained by observing the CP-processed cross section of the test sample of Comparative Example 1 at a magnification of 2000 times.

[0038] Fig. 27 This is a secondary electron image obtained by observing the CP-processed cross section of the test sample of Example 3 at a magnification of 2000 times.

[0039] Fig.28 This is a reflected electron image obtained by observing the CP-processed cross section of the test sample of Example 3 at a magnification of 2000 times.

[0040] Fig.29 This is a secondary electron image obtained by observing the CP-processed cross section of the test sample of Comparative Example 2 at a magnification of 2000 times.

[0041] Fig.30 This is a reflected electron image obtained by observing the CP-processed cross section of the test sample of Comparative Example 2 at a magnification of 2000 times.

[0042] Fig.31 The infrared spectra of the test samples of Example 1 and Example 2 were measured by the transmission method.

[0043] Fig.32 These are infrared spectra obtained by measuring the test samples of Examples 3 to 5 using the transmission method.

[0044] Fig.33 These are infrared spectra obtained by measuring the test samples of Comparative Examples 1 and 2 using the transmission method.

[0045] Fig.34 This is a secondary electron image obtained by observing the cut surface of the test sample of Example 6 at a magnification of 10,000 times.

[0046] Fig.35 This is a secondary electron image obtained by observing the cut surface of the test sample of Example 6 at a magnification of 2000 times.

[0047] Fig.36 This is a secondary electron image obtained by observing the cut surface of the test sample of Comparative Example 3 at a magnification of 10,000 times.

[0048] Fig.37 This is a secondary electron image obtained by observing the cut surface of the test sample of Comparative Example 3 at a magnification of 2000 times.

[0049] Fig.38This is a secondary electron image obtained by observing the cut surface of the test sample of Example 7 at a magnification of 10,000 times.

[0050] Fig.39 This is a secondary electron image obtained by observing the cut surface of the test sample of Example 7 at a magnification of 2000 times.

[0051] Fig.40 This is a secondary electron image obtained by observing the cut surface of the test sample of Comparative Example 4 at a magnification of 10,000 times.

[0052] Fig.41 This is a secondary electron image obtained by observing the cut surface of the test sample of Comparative Example 4 at a magnification of 2000 times.

[0053] Fig.42 This is the SEM image of the Na3AlF6 powder obtained in Example 8.

[0054] Fig.43 This is a SEM image of the Na3AlF6 powder obtained by heat treatment at 300°C in Example 9.

[0055] Fig.44 This is a SEM image of the Na3AlF6 powder obtained by heat treatment at 400°C in Example 10.

[0056] Fig.45 This is a SEM image of the Na3AlF6 powder obtained by heat treatment at 500°C in Example 11.

[0057] Fig.46 It is the XRD spectrum of the Na3AlF6 powder obtained in each example.

[0058] Fig.47 This is a secondary electron image of the structure formed by the Na3AlF6 powder of Example 9.

[0059] Fig.48 This is a reflected electron image of a structure formed from Na3AlF6 powder of Example 9.

[0060] Fig.49 This is a secondary electron image of the structure formed by the Na3AlF6 powder of Example 10.

[0061] Fig.50 This is a reflected electron image of a structure formed from the Na3AlF6 powder of Example 10.

[0062] Fig.51 This is a secondary electron image of the structure formed by the Na3AlF6 powder of Example 11.

[0063] Fig.52This is a reflected electron image of a structure formed from the Na3AlF6 powder of Example 11.

[0064] Fig.53 This is a graph comparing the linear transmittance of the structured body obtained in each example.

[0065] Fig.54 It is a graph showing the relationship between the heat treatment temperature and the relative density.

[0066] Fig.55 This is a graph showing the relationship between the heat treatment temperature and the linear transmittance.

[0067] Fig.56 This is the TG curve obtained by performing thermogravimetric analysis on Example 8 and Example 10.

[0068] Fig.57 It is a graph which shows the relationship between the 1st weight loss rate and the 2nd weight loss rate. DETAILED DESCRIPTION

[0069] Hereinafter, the structure, infrared detection device, light emitting device and method for manufacturing the structure of the present embodiment will be described in detail using the drawings. It should be noted that the dimensional ratios in the drawings are sometimes exaggerated for convenience of description and are different from the actual ratios.

[0070] [Structure]

[0071] like Figure 1 As shown, the structure 1 of this embodiment includes a base material 10. The base material 10 includes a continuous phase 11 of a polycrystalline composite fluoride. The structure 1 of this embodiment is a ceramic structure.

[0072] The complex fluoride contains an alkali metal. The complex fluoride may contain, for example, at least one alkali metal selected from the group consisting of lithium, sodium, potassium, rubidium and cesium. Alkali metal fluorides have high solubility in water, but complex fluorides containing alkali metals have low solubility in water. Regarding the solubility of alkali metal fluorides in 100 g of water at 25°C, for example, LiF is 0.134 g, NaF is 4.13 g, KF is 102 g, RbF is 300 g, and CsF is 573 g. On the other hand, regarding the solubility of complex fluorides containing alkali metals in 100 g of water at 25°C, for example, Na3AlF6 is 0.042 g, and NaMgF3 is 0.025 g.

[0073] The composite fluoride may contain fluorine, alkali metals, and at least one additional metal selected from the group consisting of alkaline earth metals, aluminum, gallium, indium, zinc and yttrium as main components. Specifically, the additional metal may contain at least one metal selected from the group consisting of magnesium, calcium, strontium, barium, aluminum, gallium, indium, zinc and yttrium. This composite fluoride can improve the transmittance of infrared light due to its low anisotropy of refractive index. In addition, the inorganic substance containing these metal elements can be easily formed into structure 1 by a pressurized heating method as described later. It should be noted that the main component here refers to the total content of fluorine, alkali metals and additional metals contained in the composite fluoride, which is more than 80% in molar ratio. The above-mentioned total content can be more than 85%, more than 90%, more than 95%, or 100%.

[0074] Specifically, the composite fluoride may include at least one of A3AlF6 and ABF3 (herein, in the above composition formula, A represents one or more alkali metals, and B represents one or more alkaline earth metals). A3AlF6 may, for example, include at least one selected from the group consisting of Li3AlF6, Li2NaAlF6, Li2KAlF6, Na3AlF6, Na2LiAlF6, Na2KAlF6, K3AlF6, K2LiAlF6, and K2NaAlF6. ABF3 may, for example, include at least one selected from the group consisting of LiMgF3, NaMgF3, KMgF3, LiCaF3, NaCaF3, and KCaF3. More specifically, the composite fluoride may include at least one selected from the group consisting of Na3AlF6, K2NaAlF6, and NaMgF3. Na3AlF6 and K2NaAlF6 have cryolite-type crystal structures, and NaMgF3 has a perovskite-type crystal structure, and are materials with small refractive index anisotropy due to crystal orientation, and therefore are preferred from the perspective of infrared transmission.

[0075] The composite fluoride may contain fluorine, alkali metals and aluminum as main components. It should be noted that the main component here refers to the total content of fluorine, alkali metals and aluminum contained in the composite fluoride being 80% or more in molar ratio. The above total content may be 85% or more, 90% or more, 95% or more, or 100%. The composite fluoride may contain, for example, sodium hexafluoroaluminate (Na3AlF6). Na3AlF6 is also known as a component of cryolite. The anisotropy of the refractive index of Na3AlF6 is small. Therefore, the transmittance of infrared light is excellent.

[0076] The composite fluoride can replace a part of its constituent anions with hydroxide ions and oxide ions. For example, in the case of composite fluoride particles obtained by liquid phase synthesis, sometimes a part of the composite fluoride ions is replaced by at least one of the hydroxide ions and the oxide ions. In the case where the composite fluoride has a hydroxyl group, the hydroxyl group absorbs infrared light of a specific wavelength. Therefore, in the case of using the structure 1 as a sensor, the sensor sensitivity can be improved by cutting off unnecessary wavelengths. In addition, in the case where the structure 1 contains a hydroxyl group, the transmittance fluctuation caused by humidity becomes smaller, and the sensor becomes less susceptible to the influence of humidity.

[0077] The structure 1 contains 85% by mass or more of inorganic substances. Therefore, compared with the case of using a resin, a structure 1 that is not easily degraded over time and has high infrared transmittance can be obtained. It should be noted that the inorganic substance includes the above-mentioned composite fluoride. In addition, the structure 1 may contain 90% by mass or more of inorganic substances, or may contain 95% by mass or more. The structure 1 may contain less than 100% by mass of inorganic substances.

[0078] The composite fluoride is a polycrystalline. Since the composite fluoride is a polycrystalline, it is excellent from the perspective of gas barrier properties and durability. The structure 1 may contain more than 50% by mass of a polycrystalline composite fluoride. In this case, the obtained structure 1 becomes a structure that is easy to effectively utilize the characteristics of the composite fluoride. By containing more than 50% by mass of the composite fluoride, the structure has higher moisture resistance than alkali metal fluorides. In addition, since the mass ratio of the composite fluoride is high, the ratio of the parts with different refractive indices in the structure 1 is reduced, so that light scattering can be suppressed and the infrared transmittance of the structure 1 can be improved. In the structure 1, the mass ratio of the composite fluoride can be more than 60%, or more than 70%, or more than 80%, or more than 90%, or more than 95%.

[0079] like Figure 2 As shown, the base material 10 may include a continuous phase 11 and a plurality of composite fluoride particles 12. The continuous phase 11 may exist between adjacent composite fluoride particles 12. The continuous phase 11 may be combined with the plurality of composite fluoride particles 12, respectively. The continuous phase 11 may directly contact the composite fluoride particles 12. In addition, the continuous phase 11 may cover at least a portion of the surface of each of the plurality of composite fluoride particles 12, or may cover the entire surface of each of the plurality of composite fluoride particles 12. The plurality of composite fluoride particles 12 may be combined with each other. The composite fluoride particles 12 may be in a point contact state or in a surface contact state where the surfaces of the composite fluoride particles 12 are in contact with each other.

[0080] The composite fluoride particles 12 may be composed of the same material as the composite fluoride constituting the continuous phase 11 as described above. The inorganic material constituting the composite fluoride particles 12 may be crystalline or amorphous. From the viewpoint of gas barrier properties or durability, the inorganic material constituting the composite fluoride particles 12 is preferably crystalline. In addition, from the viewpoint of light transmittance, the inorganic material constituting the composite fluoride particles 12 is preferably amorphous. It should be noted that, in the case of being crystalline, the composite fluoride particles 12 may be single crystal or polycrystalline.

[0081] The average particle size of the plurality of composite fluoride particles 12 is preferably not less than 10 nm and not more than 50 μm. When the average particle size of the composite fluoride particles 12 is not more than 50 μm, the light transmittance of the structure 1 is increased. In addition, when the average particle size of the composite fluoride particles 12 is within this range, the composite fluoride particles 12 are firmly bonded to each other, and the strength of the structure 1 can be improved. In addition, when the average particle size of the composite fluoride particles 12 is within this range, the ratio of pores existing inside the structure 1 as described later is made to be less than 30%. In addition, the size of the pores generated between the composite fluoride particles 12 becomes smaller. Therefore, the strength of the structure 1 can be improved. From the perspective of improving the light transmittance of the structure 1, the average particle size of the plurality of composite fluoride particles 12 is more preferably not more than 10 μm, further preferably not more than 2 μm, particularly preferably not more than 1 μm, and most preferably not more than 500 nm. The average particle size of the plurality of composite fluoride particles 12 can be, for example, not less than 1 nm or not less than 10 nm. It should be noted that in this specification, the value of "average particle size" is, unless otherwise specified, a value calculated as the average value of the particle sizes of particles observed in several to dozens of fields of view using observation means such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).

[0082] The structure 1 may contain impurities generated during the manufacturing process. The impurities may be, for example, raw materials for generating complex fluorides, and may contain elements constituting complex fluorides. The elements contained in the impurities may, for example, contain at least one element selected from the group consisting of fluorine, alkali metals, and the above-mentioned additional metals. The impurities may contain oxygen compounds, halides, hydroxides, nitrides, or carbides containing oxides composed of one metal element. The impurities may be crystalline or amorphous.

[0083] The refractive index difference between the composite fluoride and the impurity may be 0.1 or less. When the refractive index difference is 0.1 or less, the scattering of light can be suppressed, and a structure with high transmittance can be prepared. The lower limit of the refractive index difference is not particularly limited. The refractive index difference may be 0.08 or less, or 0.04 or less.

[0084] The structure 1 may include, for example, an organic substance such as resin particles. As described later, the structure 1 can be obtained by heating to 100 to 300° C. while applying pressure, so a component with low heat resistance can be added to the structure 1. In addition, the structure 1 is not limited to components with low heat resistance such as organic substances, and may include inorganic compounds other than complex fluorides and impurities in order to impart functionality.

[0085] The porosity in the cross section of the structure 1 is 30% or less. That is, the porosity of pores larger than 0 nm in the cross section of the structure 1 is 30% or less. Specifically, when observing the cross section of the structure 1, the average value of the ratio of pores per unit area is 30% or less. When the porosity is 30% or less, the number of pores inside the base portion decreases, so a solidified body with high strength is obtained. It should be noted that the porosity in the cross section of the structure 1 is preferably 20% or less, more preferably 10% or less, and further preferably 5% or less. The smaller the porosity in the cross section of the structure 1, the more cracks starting from the pores can be suppressed, so the strength of the structure 1 can be improved. Furthermore, the smaller the porosity in the cross section of the structure 1, the more light scattering caused by the pores can be suppressed, so the transmittance of the structure 1 can be improved.

[0086] In this specification, the porosity can be calculated as follows. First, observe the cross section of the structure 1 to distinguish the pores from the parts other than the pores. Then, measure the area of ​​the pores per unit area and calculate the ratio of the pores per unit area. The porosity is the average value of the ratio of the pores per unit area calculated at multiple locations. When observing the cross section of the structure 1, an optical microscope, a scanning electron microscope (SEM) or a transmission electron microscope (TEM) can be used. In addition, the unit area and the area of ​​the pores per unit area can be measured by binarizing the image obtained by observation with a microscope.

[0087] The median value of the pore diameter of the structure 1 is 500nm or less. When the median value of the pore diameter is 500nm or less, the scattering of light caused by the pores can be suppressed, thereby becoming a structure 1 with high transmittance. The median value of the pore diameter is preferably 300nm or less, more preferably 200nm or less, and further preferably 100nm or less. It should be noted that in this specification, the median value of the pore diameter represents the pore diameter when the cumulative value of the pore diameter distribution on an area basis is 50%. The pore diameter represents the diameter of a true circle when the shape of the pores in the cross section of the structure 1 is assumed to be a true circle.

[0088] In the cross section of the structure 1, the area ratio of pores having a pore diameter greater than 500 nm is preferably 1% or less per unit area. In this case, the scattering of light caused by the pores can be suppressed, thereby forming a structure with a higher transmittance. The above area ratio is more preferably 0.5% or less, further preferably 0.1% or less, and particularly preferably 0.0%. It should be noted that the above area ratio of 0.0% means that no pores having a median pore diameter greater than 500 nm are observed per unit area.

[0089] The structure 1 has infrared light transmittance. In the target wavelength band, the linear transmittance of the structure 1 may have a wavelength bandwidth above a prescribed value. The linear transmittance of the structure 1 may be obtained by measuring using a transmission method using an FT-IR (Fourier transform infrared spectroscopy) device. The linear transmittance of the infrared transmission spectrum is converted based on the Lambert-Beer law in a manner that becomes a linear transmittance at a thickness of 1 mm. In addition, the wavelength bandwidth can be obtained by measuring in the target wavelength band a wavelength bandwidth in which the linear transmittance reaches a prescribed value or above. The wavelength bandwidth may be a wavelength bandwidth in which the linear transmittance continuously reaches a prescribed value or above, or may be a total wavelength bandwidth in which the linear transmittance continuously and intermittently reaches a prescribed value or above. That is, the wavelength bandwidth is the total wavelength bandwidth in which the linear transmittance reaches a prescribed value or above in the target wavelength band. Therefore, in the case in which the linear transmittance intermittently reaches a prescribed value or above, the wavelength band in which the linear transmittance reaches a prescribed value or above may be separated from each other in the target wavelength band. It should be noted that the wavelength bandwidth is preferably a wavelength bandwidth in which the linear transmittance continuously reaches a prescribed value or above.

[0090] In the target wavelength band of 3 μm to 10 μm, the wavelength bandwidth in which the linear transmittance exceeds 10% continuously per 1 mm of the thickness of the structure 1 can be 0.1 μm or more. Such a structure 1 can be expected to be used as an infrared transmission filter. It should be noted that the target wavelength band can be 8 μm or less, or 6 μm or less. In addition, the wavelength bandwidth in which the linear transmittance exceeds 10% can be 0.5 μm or more, or 1 μm or more, or 1.5 μm or more, or 2 μm or more. In addition, the wavelength bandwidth in which the linear transmittance exceeds 10% can be 3 μm or less. The linear transmittance in the above wavelength bandwidth can exceed 20%, 30%, 40%, 50% or 60%. For example, in the target wavelength band of 3 μm to 5 μm, the wavelength bandwidth in which the linear transmittance exceeds 50% continuously can be 0.1 μm or more. The upper limit of the linear transmittance in the above wavelength bandwidth is not particularly limited, for example, 100%.

[0091] At a wavelength of 4 μm, the linear transmittance per 1 mm thickness of the structure 1 may exceed 20%, 30%, 40%, 50% or 60%. In the wavelength range of 3.8 μm to 4.4 μm, the average linear transmittance per 1 mm thickness of the structure 1 may be 60% or more, or 65% or more.

[0092] In addition, at a wavelength of 3.8 to 4.4 μm, the average value of the linear transmittance per 1 mm thickness of the structure 1 may exceed 20%, 30%, 40%, 50%, or 60%. In addition, in the entire range of wavelengths of 3.8 to 4.4 μm, the average value of the linear transmittance per 1 mm thickness of the structure 1 may exceed 20%, 30%, 40%, 50%, or 60%.

[0093] The weight loss rate when the structure 1 is heated from 200° C. to 500° C. can be 0.5% or less. The amount of hydroxyl groups and water molecules inside the structure 1 is small, which can suppress infrared absorption and scattering caused by hydroxyl groups and water molecules. Therefore, the infrared transmittance can be further improved. The weight loss rate can be 0.4 or less, or 0.3 or less. In addition, the weight loss rate can be 0% or more.

[0094] The weight loss rate can be measured by TG (thermogravimetric analysis) in accordance with JIS K7120-1987. The weight loss rate when heated from 200°C to 500°C can be calculated by the following formula (1).

[0095] Weight loss rate (%) = (((mass of composite fluoride particles at 200°C) - (mass of composite fluoride particles at 500°C)) / (mass of composite fluoride particles at 200°C)) × 100 (1)

[0096] The structure 1 may be an infrared transmission filter. By using the structure 1 as an infrared transmission filter, an infrared detection device and a light-emitting device that can suppress diffuse reflection of infrared light caused by pores can be provided. In the case where the structure 1 can transmit light in a specific infrared region as a single layer, for example, it is not necessary to stack multiple dielectrics like an interference filter or to separately provide a light-shielding filter to improve sensor sensitivity, and specific infrared light can be transmitted.

[0097] The thickness t of the structure 1 is greater than 10 μm. The structure 1 of the present embodiment is formed by a pressurized heating method as described later. Therefore, even if the thin films are not stacked to form the structure 1, a block having a thickness of greater than 10 μm can be easily formed. It should be noted that the thickness of the structure 1 can be greater than 100 μm, or greater than 500 μm, or greater than 1 mm, or greater than 1 cm. The upper limit of the thickness of the structure 1 is not particularly limited, and can be, for example, 50 cm.

[0098] When the structure 1 is used as an infrared transmission filter, its shape is not particularly limited. It can be a flat plate, a concave lens, or a convex lens. When a lens shape is to be given, light can be incident vertically on the dielectric stacked bandpass filter, thereby eliminating the light incident angle dependence of the dielectric stacked bandpass filter. In addition, a fine structure with an anti-reflection function can be formed on the surface of the structure 1.

[0099] As described above, the structure 1 has a base material 10 including a continuous phase 11 of a polycrystal of a composite fluoride, the composite fluoride including an alkali metal. The structure 1 includes 85% by mass or more of an inorganic substance, the structure 1 includes 50% by mass or more of a polycrystal of a composite fluoride, the porosity of the structure 1 is 30% or less, the median value of the pore diameter of the structure 1 is 500 nm or less, and the thickness of the structure 1 is 10 μm or more.

[0100] According to this configuration, the structure is not easily dissolved in water and can be manufactured by a simple low-temperature process. Therefore, it is suitable for use in infrared transmission windows of gas sensors and flame detection sensors.

[0101] [Infrared detection device]

[0102] Next, the infrared detection device 100 of this embodiment is used. Figure 3 The infrared detection device 100 is as follows. Figure 3 As shown, the infrared detection device 100 includes the above-mentioned structure 1. In addition, the infrared detection device 100 further includes an infrared detection element 110, an IC element 120, a substrate 130, and a metal case 150.

[0103] The infrared detection element 110 and the IC element 120 are mounted on the substrate 130 via a die bonding material 131. The infrared detection element 110 and the IC element 120 are electrically connected to each other via a lead 140. The infrared detection element 110 is connected to a circuit wiring (not shown) of the substrate 130 via the lead 140.

[0104] The infrared detection element 110 receives infrared rays, converts the heat energy of the received infrared rays into electrical energy, and outputs an electrical signal corresponding to the amount of the received infrared rays to the IC element 120. The infrared detection element 110 may be a thermal infrared detection element such as a pyroelectric element, a thermopile infrared detection element, or a bolometer infrared detection element, or a quantum infrared detection element.

[0105] The IC element 120 includes an amplifier circuit for amplifying the electric signal output from the infrared detection element 110 and a determination circuit for determining that a flame exists when the electric signal amplified by the amplifier circuit exceeds a threshold value.

[0106] The metal shell 150 is mounted on the substrate 130. The metal shell 150 surrounds the infrared detection element 110 and the IC element 120, and the infrared detection element 110 and the IC element 120 are sealed by the substrate 130 and the metal shell 150. The metal shell 150 includes an upper wall 151 and a side wall 152. An opening is provided in the upper wall 151, and the opening is covered by the structure 1. The structure 1 is arranged in a manner opposite to the infrared detection element 110, and the infrared detection element 110 is provided on the substrate 130 to receive infrared rays passing through the structure 1. The side wall 152 connects the edge of the upper wall 151 to the edge of the substrate 130.

[0107] The infrared rays emitted by the flame or the like pass through the structure 1 and are received by the infrared detection element 110. The infrared detection element 110 outputs an electrical signal corresponding to the amount of infrared rays received to the IC element 120. The IC element 120 determines whether there is a flame based on the electrical signal. In this way, the infrared detection device 100 can detect the flame using the infrared rays emitted by the flame.

[0108] It should be noted that gas molecules such as inorganic gases such as SO2, CO2, PH3, N2O and NO have characteristic absorption characteristics in the mid-infrared region. In addition, these gas molecules emit corresponding infrared rays at high temperatures. Therefore, the structure 1 of the present embodiment is not limited to CO2, and can also be used as a sensor for gases having characteristic absorption characteristics in the infrared region. Specifically, the structure 1 of the present embodiment is useful as an infrared transmission window because of its high infrared transmittance.

[0109] It should be noted that, although the present embodiment describes an example of using the infrared detection device 100 in a flame sensor for detecting flames, the use of the infrared detection device 100 is not limited to this method. The infrared detection device 100 can also be used in a human body sensing sensor, a biosensor, an anti-theft sensor, a gas sensor, a non-contact thermometer, a solid-state imaging device or a camera module, etc.

[0110] [Light-emitting device]

[0111] Next, for the light emitting device 200 of this embodiment, use Figure 4 The light emitting device 200 is as follows. Figure 4 As shown, the light emitting device 200 includes the structure 1. In addition, the light emitting device 200 includes the structure 1 and a light source 210 for emitting light including infrared rays. The light source 210 may include an LED, a xenon lamp, a laser diode, or a combination thereof.

[0112] Since the light emitting device 200 includes the structure 1, a part of the infrared rays emitted from the light source 210 can be cut off by the structure 1. Therefore, according to the light emitting device 200 of this embodiment, light having a specific wavelength can be emitted. The light emitting device 200 can be used, for example, as a light emitting device for gas detection, a light emitting device for inspection, a light emitting device for a surveillance camera, a light emitting device for hair removal, a light emitting device for curing infrared curing resin, and the like.

[0113] [Method for manufacturing structure]

[0114] (First Embodiment)

[0115] Next, the manufacturing method of the structure 1 of the first embodiment is described. The structure 1 can be manufactured by pressurizing and heating a raw material containing composite fluoride particles. By using this pressurization and heating method, the composite fluoride particles are deformed and combined with each other, so that a structure 1 with a small porosity can be formed. The raw material containing fluoride particles can include a process of generating a plurality of composite fluoride particles, a process of separating, a process of heating, and a process of adding water.

[0116] The process of generating a plurality of composite fluoride particles is specifically, first, by mixing and reacting a first metal compound as an alkali metal fluoride with a second metal compound different from a fluoride, thereby preparing composite fluoride particles. The mixing method of the alkali metal fluoride and the second metal compound is not particularly limited, and can be dry mixing or wet mixing. The solutions can be mixed by adding a second metal compound solution to an alkali metal fluoride solution, or by adding an alkali metal fluoride solution to a second metal compound solution. In addition, two liquids can be mixed simultaneously and in equal amounts in portions using a microchannel or the like. As a solvent, for example, water can be used.

[0117] The concentration of the alkali metal fluoride after mixing with the second metal compound can be appropriately adjusted. The concentration of the alkali metal fluoride can be 100 mM or more, or 200 mM or more. The concentration of the alkali metal fluoride can be 1000 mM or less. The concentration of the second metal compound can be 20 mM or more, or 40 mM or more. The concentration of the second metal compound can be 200 mM or less. Since there is a tendency that the greater the concentration of these raw materials, the smaller the particle size, the transmittance of the structure 1 can be improved.

[0118] Examples of the alkali metal contained in the alkali metal fluoride include lithium, sodium, potassium, rubidium, and cesium. Specifically, the alkali metal fluoride may contain at least one alkali metal selected from the group consisting of lithium fluoride, sodium fluoride, potassium fluoride, rubidium fluoride, and cesium fluoride.

[0119] The second metal compound is at least one selected from the group consisting of metal chlorides, metal nitrates, metal sulfates and metal organic acid salts, and may contain metal salts other than metal fluorides. The metal contained in the second metal compound may be at least one selected from the group consisting of alkaline earth metals, aluminum, gallium, indium, zinc and yttrium. The second metal compound may contain aluminum chloride, for example.

[0120] The separation step separates the generated multiple composite fluoride particles. When the second metal compound is a metal chloride, a metal nitrate, a metal sulfate, or a metal organic acid salt, when the alkali metal fluoride and the second metal compound are mixed, in addition to the composite fluoride, alkali metal chloride, nitrate, sulfate, and metal organic acid salt are also generated as by-products. Therefore, a washing operation to remove the by-products can be implemented. The alkali metal compound can be removed by washing with a solvent such as water during the operation of filtering or centrifugal separation.

[0121] The heating process heats the separated multiple composite fluoride particles at a temperature of 200°C or above. By setting the heating temperature to be above 200°C, the water content inside the composite fluoride particles is reduced. As a result, the absorption of infrared light caused by the hydroxyl groups and water inside the structure 1 is reduced, and the transmittance of the structure 1 can be improved. The heating temperature of the composite fluoride particles can be above 300°C, above 350°C, above 400°C, above 450°C, or above 500°C. The heating temperature of the composite fluoride particles can be below 900°C, below 800°C, below 700°C, below 600°C, or below 550°C. The heating time of the composite fluoride particles can be above 0.5 hours, above 1 hour, or above 1.5 hours. In addition, the heating time of the composite fluoride particles can be below 24 hours, below 12 hours, below 6 hours, or below 3 hours.

[0122] The method for producing composite fluoride powder can be dried after removing by-products and separating composite fluoride particles as needed. The drying temperature is not particularly limited and can be implemented at a temperature below the melting point of the composite fluoride. The drying temperature can be, for example, above 40°C, above 80°C, above 100°C, or above 200°C. In addition, the drying temperature can be, for example, below 600°C, below 400°C, below 300°C, or below 200°C. The drying time of the composite fluoride particles can be above 0.5 hours, above 1 hour, or above 1.5 hours. In addition, the drying time of the composite fluoride particles can be below 24 hours, below 12 hours, below 6 hours, or below 3 hours.

[0123] The raw material may contain hydration water in addition to the complex fluoride. In addition, the raw material may contain byproducts such as simple fluoride, oxide, and hydroxide containing a single metal element as unavoidable impurities.

[0124] Next, the raw material containing the composite fluoride particles is filled into the interior of the mold. After the raw material is filled into the mold, the mold can be heated as needed. Then, by applying pressure to the raw material inside the mold, the interior of the mold is made into a high-pressure state. At this time, while the composite fluoride particles are densified, the composite fluoride particles are bonded to each other.

[0125] The heating and pressurizing conditions are not particularly limited as long as they are conditions that can densify the composite fluoride particles. For example, it is preferred that the raw material is heated to 50 to 300° C. and then pressurized at a pressure of 10 to 600 MPa. It should be noted that the temperature when the raw material is heated is more preferably 80 to 250° C., and further preferably 100 to 200° C. In addition, the pressure when the raw material is pressurized is more preferably 50 to 600 MPa.

[0126] Then, by taking out the molded body from the inside of the mold, the structure 1 can be obtained. It is considered that by heating and pressurizing the raw material containing composite fluoride particles containing at least one of hydroxyl groups and water molecules, the composite fluoride particles react with each other via the hydroxyl groups or water molecules to form a continuous phase 11 of a polycrystalline composite fluoride containing an alkali metal. In this way, the above-mentioned structure 1 can be formed.

[0127] By the reaction based on pressurization and heating as described above, a structure 1 having a dense structure can be obtained. In addition, as a method for forming an aggregate of inorganic particles, a method of only pressing the powder of inorganic particles to form a pressed powder body and then sintering it at a high temperature (for example, above 1700°C) can also be considered. However, even if the pressed powder body of inorganic particles is sintered at a high temperature, a large number of pores will exist in the resulting structure 1, and not only the mechanical strength will become insufficient, but also the transmittance will become insufficient due to the scattering of light. In addition, when the inorganic particles are sintered at a high temperature, dense temperature control is required, so the manufacturing cost will increase.

[0128] In contrast, the manufacturing method of the present embodiment heats and presses the raw material containing composite fluoride particles containing at least one of hydroxyl groups and water molecules, thereby obtaining a dense structure 1 having excellent transmittance. Furthermore, the manufacturing method of the present embodiment can be obtained by heating and pressurizing at 50° C. to 300° C., so that precise temperature control is not required, and manufacturing costs can be reduced.

[0129] Thus, the method for producing the structure 1 of the present embodiment includes the steps of pressurizing and heating the raw material including the composite fluoride. According to the method for producing the structure 1 of the present embodiment, the structure 1 can be produced by a simple low-temperature process.

[0130] (Second Embodiment)

[0131] Next, the manufacturing method of the structure 1 of the second embodiment is described. The structure 1 can also be manufactured by pressurizing and heating a raw material containing first fluoride particles containing an alkali metal and second fluoride particles containing a metal other than an alkali metal. By using this pressurization and heating method, the fluoride particles are bonded to each other while forming a composite fluoride, so that a structure 1 with a small porosity can be formed.

[0132] The first fluoride particles contain an alkali metal. Examples of the alkali metal contained in the first fluoride particles include lithium, sodium, potassium, rubidium, and cesium. Specifically, the first fluoride particles may contain at least one metal fluoride selected from the group consisting of lithium fluoride, sodium fluoride, potassium fluoride, rubidium fluoride, and cesium fluoride.

[0133] The second fluoride particles contain metal elements other than alkali metals. The metal elements other than alkali metals are not particularly limited and may be at least one selected from the group consisting of alkaline earth metals, aluminum, gallium, indium, zinc and yttrium. Specifically, the metal elements other than alkali metals may include at least one metal selected from the group consisting of magnesium, calcium, strontium, barium, aluminum, gallium, indium, zinc and yttrium. The second fluoride particles may include at least one metal fluoride selected from the group consisting of magnesium fluoride (MgF2), calcium fluoride (CaF2), strontium fluoride (SrF2), barium fluoride (BaF2), aluminum fluoride (AlF3), gallium fluoride (GaF3), indium fluoride (InF3), yttrium fluoride (YF3), and zinc fluoride (ZnF2).

[0134] Next, a solvent is added to the raw material containing the first fluoride particles and the second fluoride particles. The solvent is not particularly limited, and for example, a solvent that can dissolve a portion of the first fluoride particles and the second fluoride particles when the raw material is pressurized and heated can be used. As such a solvent, for example, water can be used.

[0135] The raw material including the first fluoride particles and the second fluoride particles can be pressurized and heated in the same manner as in the above embodiment to form a structure 1. The first fluoride particles and the second fluoride particles react in a solvent by pressurizing and heating to form a continuous phase 11 of a polycrystalline composite fluoride including an alkali metal. Thus, the above structure 1 can be formed.

[0136] As described above, the method for manufacturing the structure 1 of the present embodiment includes the steps of pressurizing and heating a raw material containing a first fluoride containing an alkali metal, a second fluoride containing a metal other than an alkali metal, and water. According to the method for manufacturing the structure 1 of the present embodiment, the structure 1 can be manufactured by a simple low-temperature process.

[0137] (Third Embodiment)

[0138] Next, the method for producing the structure 1 of the third embodiment is described. The structure 1 can also be produced by pressurizing and heating a raw material including the composite fluoride particles obtained by the method for producing the structure 1 of the first embodiment and the first fluoride particles and the second fluoride particles described in the second embodiment.

[0139] Specifically, first, a raw material is prepared by mixing composite fluoride particles with first fluoride particles and second fluoride particles. The method for mixing these particles is not particularly limited, and can be dry mixing or wet mixing. When a solvent is added to the raw material, water can be used as the solvent, for example.

[0140] The raw material including the first fluoride particles and the second fluoride particles can be pressurized and heated in the same manner as in the above embodiment to form the structure 1. The first fluoride particles and the second fluoride particles react in the solvent by pressurizing and heating, and are bonded to each other while forming a composite fluoride. In addition, the composite fluoride particles are bonded to each other while being deformed. Thus, the structure 1 can be formed.

[0141] As described above, the method for manufacturing the structure 1 of the present embodiment includes the steps of pressurizing and heating a raw material, the raw material containing at least one of the following two: a first fluoride containing an alkali metal, a second fluoride containing a metal other than an alkali metal, and water; and a composite fluoride. According to the method for manufacturing the structure 1 of the present embodiment, the structure 1 can be manufactured by a simple low-temperature process.

[0142] That is, as described in the first to third embodiments, the method for manufacturing the structure 1 includes a step of pressurizing and heating a raw material under the conditions of a pressure of 10 to 600 MPa and a temperature of 50 to 300° C., the raw material containing at least one of the following two: a first fluoride containing an alkali metal, a second fluoride containing a metal other than an alkali metal, and water; and a composite fluoride containing at least one of a hydroxyl group and a water molecule. The structure 1 contains 85% by mass or more of an inorganic substance, the structure 1 contains 50% by mass or more of a polycrystal of the composite fluoride, the porosity of the structure 1 is 30% or less, the median value of the pore diameter of the structure 1 is 500 nm or less, and the thickness of the structure 1 is 10 μm or more. According to the method for manufacturing the structure 1 of these embodiments, the structure 1 can be manufactured by a simple low-temperature process.

[0143] Example

[0144] Hereinafter, the present embodiment will be described in more detail with reference to Examples and Comparative Examples, but the present embodiment is not limited to these Examples.

[0145] (Example 1)

[0146] First, sodium fluoride (NaF) powder (Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent) and aluminum fluoride (AlF3) powder (High Purity Chemical Research Institute) were prepared. Then, the sodium fluoride powder and aluminum fluoride were mixed in a pot mill in a molar ratio of 3:1, and then 20% by weight of ion exchange water was added to the total amount of powder using an agate mortar and agate pestle to mix, thereby obtaining a mixed powder.

[0147] Next, the mixed powder was put into a cylindrical molding die (Φ12) having an internal space. The mixed powder was heated and pressurized at 180°C and 400 MPa for 20 minutes. In this way, a cylindrical test sample of this example was obtained.

[0148] (Example 2)

[0149] First, sodium hexafluoroaluminate (Na3AlF6) was synthesized. Specifically, 32 mmol of sodium fluoride (NaF) powder (Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent), 4 mmol of aluminum chloride (AlCl3·6H2O) powder (Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent), and 100 mL of H2O were mixed and stirred at 25°C for 1 hour. The stirred solution was filtered using a membrane filter with a pore size of 0.1 μm, and the residue was dried at -60 to -100 kPa and 80°C for 2 hours to obtain a single-phase Na3AlF6 powder.

[0150] In addition, sodium fluoride (NaF) powder (Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent) and aluminum fluoride (AlF3) powder (High Purity Chemical Research Institute) were prepared. Then, the sodium fluoride powder, aluminum fluoride powder and Na3AlF6 powder were mixed in a molar ratio of 3:1:9 using an agate mortar and an agate pestle, and 20% by weight of ion exchange water was added relative to the total amount of the powder to obtain a mixed powder.

[0151] Next, the mixed powder was put into a cylindrical molding die (Φ12) having an internal space. The mixed powder was heated and pressurized at 180°C and 400 MPa for 20 minutes. In this way, a cylindrical test sample of this example was obtained.

[0152] (Example 3)

[0153] First, synthesize sodium hexafluoroaluminate (Na3AlF6). Specifically, 32 mmol of sodium fluoride (NaF) powder (Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent), 4 mmol of aluminum chloride (AlCl3·6H2O) powder (Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent), and 100 mL of H2O are mixed and stirred at 25°C for 1 hour. The stirred liquid is filtered using a membrane filter with a pore size of 0.1 μm, and the residue is dried at -60 to -100 kPa and 80°C for 2 hours to obtain a single-phase Na3AlF6 powder. The SEM image of the Na3AlF6 powder obtained in the synthesis is shown in FIG. Figure 5 .

[0154] Next, Na3AlF6 powder was put into a cylindrical forming mold (Φ12) having an internal space. The Na3AlF6 powder was then heated and pressurized at 180°C and 400 MPa for 20 minutes. In this way, a cylindrical test sample of this example was obtained.

[0155] (Example 4)

[0156] First, synthesize K2NaAlF6. Specifically, 32 mmol of potassium fluoride (KF) powder (Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent), 6 mmol of sodium chloride (NaCl) powder (Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent), 2 mmol of aluminum chloride (AlCl3·6H2O), and 20 mL of H2O are mixed and stirred at 25°C for 1 hour. The stirred liquid is filtered using a membrane filter with a pore size of 0.1 μm, and the residue is dried at -60 to -100 kPa and 80°C for 2 hours to obtain a single-phase K2NaAlF6 powder. The SEM image of the K2NaAlF6 powder obtained in the synthesis is shown in FIG. Figure 6 .

[0157] Next, K2NaAlF6 powder was placed into a cylindrical forming mold (Φ12) having an internal space. The K2NaAlF6 powder was then heated and pressurized at 180°C and 400 MPa for 20 minutes. In this way, a cylindrical test sample of this example was obtained.

[0158] (Example 5)

[0159] First, synthesize NaMgF3. Specifically, 48 mmol of sodium fluoride (NaF) powder (Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent), 12 mmol of magnesium chloride (MgCl2·6H2O) powder (Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent), and 100 mL of H2O are mixed and stirred at 80°C for 3 hours. The stirred liquid is filtered using a membrane filter with a pore size of 0.1 μm, and the residue is dried at -60 to -100 kPa and 80°C for 2 hours to obtain a single-phase NaMgF3 powder. The SEM image of the NaMgF3 powder obtained in the synthesis is shown in Figure 7 .

[0160] Next, NaMgF3 powder was put into a cylindrical forming die (Φ12) having an internal space. The NaMgF3 powder was then heated and pressurized at 180°C and 400 MPa for 20 minutes. In this way, a cylindrical test sample of this example was obtained.

[0161] (Comparative Example 1)

[0162] The test sample obtained in Example 1 was fired at 800° C. for 2 hours to obtain the test sample of this example.

[0163] (Comparative Example 2)

[0164] The test sample obtained in Example 3 was fired at 800° C. for 2 hours to obtain the test sample of this example.

[0165] [Evaluation of test samples]

[0166] The test samples prepared as described above were subjected to crystal structure analysis, pore observation, and measurement of porosity, pore diameter, and linear transmittance.

[0167] (Crystal Structure Analysis)

[0168] Next, the powders obtained by pulverizing the test samples of Examples 1 to 5 were measured using a powder X-ray diffraction (XRD) apparatus to obtain XRD patterns. The results are shown in Figure 8 to Figure 12In addition, the obtained XRD pattern was subjected to Rietveld analysis to determine the ratio of each component. The results are shown in Tables 1 and 2. It should be noted that in Tables 1 and 2, the units of the numerical values ​​above are mass %, and the units of the numerical values ​​in brackets below are volume %.

[0169] (Observation of Stomata)

[0170] First, a cross-section polishing process (CP process, cross-section polisher) was performed on the cross section of each test sample. Next, a scanning electron microscope (SEM) was used to observe the secondary electron image and reflected electron image of the cross section of the test sample at a magnification of 10000 times or 2000 times. The secondary electron images and reflected electron images of Examples 1 to 5 and Comparative Examples 1 to 2 are shown in FIG. Figures 13 to 30 .

[0171] (Determination of porosity and pore diameter)

[0172] Next, the reflected electron image obtained as described above is binarized to make the pore part clear. Then, the area ratio of the pore part is calculated based on the binarized image to obtain the porosity. It should be noted that the porosity is calculated for pores with pore diameters of 0 nm or more, 200 nm or more, 300 nm or more, and 500 nm or more. The results are shown in Table 3. In addition, the cumulative value of the pore diameter distribution based on the area standard is 10% (d 10 )、50%(d 50 ) and 90% (d 90 These calculation results are shown in Table 4.

[0173] (Linear transmittance)

[0174] The infrared transmission spectra of each test sample were obtained by using a FT-IR device using the transmission method. The results are shown in Figure 31 to Figure 33 It should be noted that the linear transmittance of the infrared transmission spectrum was converted based on the Lambert-Beer law so as to be the linear transmittance at a thickness of 1 mm.

[0175] Table 1

[0176]

[0177] Table 2

[0178]

[0179] Table 3

[0180]

[0181] Table 4

[0182]

[0183] As shown in Table 1, the test sample of Example 1 contains the same components as the raw materials, namely NaF and AlF3, and Na3AlF6 generated by the hydrothermal reaction. Since the raw materials of Example 1 use granular NaF and AlF3, the center of the granules may remain in an unreacted state. On the other hand, it is found that the test sample of Example 2 contains a small amount of Na5Al3F6 in addition to Na3AlF6. 14 .

[0184] As shown in Table 2, it was found that the test sample of Example 3 contained a small amount of Na5Al3F6 in addition to Na3AlF6. 14 The sample of Example 4 contains 100 mass % of K2NaAlF6 which is the same as the raw material. In addition, the sample of Example 5 also contains 100 mass % of NaMgF3 which is the same as the raw material.

[0185] As shown in Table 3, the porosity of pores larger than 500 nm was 0.27% in Example 1 and 0.00% in Examples 2 to 5. On the other hand, the porosity of pores larger than 500 nm was 3.59% in Comparative Example 1 and 6.11% in Comparative Example 2. In addition, as shown in Table 4, the median values ​​of the pore diameters (d 50 ) is very small compared with Comparative Examples 1 and 2.

[0186] like Fig.31 As shown, the linear transmittance continuously exceeds 10% in the range of 4.30 μm to 5.80 μm (wavelength bandwidth 1.5 μm) in Example 1 and in the range of 3.62 μm to 5.96 μm (wavelength bandwidth 2.34 μm) in Example 2. Fig.32 As shown, the linear transmittance continuously exceeds 10% in the range of 3.50 μm to 5.88 μm (wavelength bandwidth 2.38 μm) in Example 3, in the range of 3.74 μm to 5.62 μm (wavelength bandwidth 1.88 μm) in Example 4, and in the range of 3.78 μm to 5.62 μm (wavelength bandwidth 1.84 μm) in Example 5. On the other hand, Fig.33 As shown, the linear transmittance of Comparative Examples 1 and 2 is less than 1% in the entire wavelength range of 3 μm to 10 μm.

[0187] From these results, it was found that the test samples of Examples 1 to 5 had higher linear transmittance than the test samples of Comparative Examples 1 and 2. This is considered to be because the median value of the pore diameter of the structure of the test samples of Examples 1 to 5 was 500 nm or less, and light scattering due to coarse pores was less.

[0188] In addition, the test sample of Example 2 has a higher infrared transmittance than the test sample of Example 1. One possible reason is that the ratio of the remaining unreacted raw material in the test sample of Example 2 is small.

[0189] Next, a test sample formed by pressurization and heating and a test sample formed by pressurization and firing were prepared as follows.

[0190] (Example 6)

[0191] The same process as in Example 3 was used to obtain a cylindrical test sample of this example.

[0192] (Example 7)

[0193] The same process as in Example 1 was followed to obtain a cylindrical test sample of this example.

[0194] (Comparative Example 3)

[0195] The Na3AlF6 powder synthesized in Example 6 was put into a molding die. Next, the Na3AlF6 powder was pressurized at room temperature (25°C) and 50 MPa. The cylindrical powder compact obtained in this way was sintered at 800°C for 2 hours.

[0196] (Comparative Example 4)

[0197] The mixed powder prepared in Example 7 was placed in a molding die. Next, the mixed powder was pressurized at room temperature (25° C.) and 50 MPa. The cylindrical powder compact obtained in this way was sintered at 800° C. for 2 hours.

[0198] (Structural Observation)

[0199] The cut surfaces of the test samples of Examples 6 and 7 and Comparative Examples 3 and 4 were observed at a magnification of 10,000 or 2,000 times using a scanning electron microscope (SEM). Their secondary electron images are shown in FIG. Figure 34 to Figure 41 It should be noted that gold was sputtered on the observation surface of the test sample.

[0200] The pores of the test sample of Comparative Example 3 were larger than those of the test sample of Example 6. Similarly, the pores of the test sample of Comparative Example 4 were larger than those of the test sample of Example 7. From these results, it can be seen that the test sample formed by pressurization and heating is denser than the test sample formed by pressurization and firing.

[0201] Next, in order to confirm the influence of heat treatment on Na3AlF6 powder, the structure of the following example was produced.

[0202] (Example 8)

[0203] The same process as in Example 3 was used to obtain a cylindrical test sample of this example.

[0204] (Example 9)

[0205] First, synthesize sodium hexafluoroaluminate (Na3AlF6). Specifically, 24 mmol of sodium fluoride (NaF) powder (Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent), 3 mmol of aluminum chloride (AlCl3·6H2O) powder (Fujifilm Wako Pure Chemical Industries, Ltd., special grade reagent), and 100 mL of H2O are mixed and stirred at 28°C for 20 hours. The stirred liquid is filtered using a membrane filter with a pore size of 0.1 μm, and the residue is dried at -60 to -100 kPa and 80°C for 2 hours. Then, the obtained powder is crushed in a mortar and heat-treated in the air at 300°C for 2 hours to obtain Na3AlF6 powder.

[0206] 10% by mass of water relative to the heat-treated Na3AlF6 powder is added to the Na3AlF6 powder. Next, the water-added Na3AlF6 powder is put into a cylindrical forming mold (Φ12) having an internal space. Then, the water-added Na3AlF6 powder is heated and pressurized at 180°C, 400MPa, and 20 minutes. In this way, a cylindrical test sample of this example is obtained.

[0207] (Example 10)

[0208] A test sample was prepared in the same manner as in Example 9 except that the heat treatment temperature was set to 400°C instead of 300°C.

[0209] (Example 11)

[0210] A test sample was prepared in the same manner as in Example 9 except that the heat treatment temperature was set to 500°C instead of 300°C.

[0211] [evaluate]

[0212] (SEM image of Na3AlF6 powder)

[0213] The Na3AlF6 powders obtained in the synthesis of Examples 8 to 11 after heat treatment for 2 hours were observed using a scanning electron microscope (SEM). These SEM images are shown in Figure 42 to Figure 45 .

[0214] (Crystal Structure Analysis)

[0215] The XRD patterns of the Na3AlF6 powders obtained in each example after 2 hours of heat treatment were obtained using a powder X-ray diffraction (XRD) apparatus. Fig.46 .

[0216] (Observation of Stomata)

[0217] As described above, a scanning electron microscope (SEM) was used to observe the secondary electron image and reflected electron image of the cross section of the test sample at a magnification of 10,000 times. The secondary electron image and reflected electron image of Example 9 are shown in Fig.47 and Fig.48 The secondary electron image and reflected electron image of Example 10 are shown in Fig.49 and Fig.50 The secondary electron image and reflected electron image of Example 11 are shown in Fig.51 and Fig.52 .

[0218] (Determination of porosity and pore diameter)

[0219] The porosity was measured from the obtained reflected electron image in the same manner as above. It should be noted that the porosity was determined for pores with a pore diameter of 5 nm or more. The results are shown in Table 5. In addition, the cumulative value of the pore diameter distribution based on the area standard is 10% (d 10 )、50%(d 50 ) and 90% (d 90 These calculation results are shown in Table 5.

[0220] (Relative density)

[0221] First, the volume and mass of the structure were measured to calculate the apparent density of the structure. Next, the apparent density of the test sample was divided by the density of cryolite (2.98 g / cm 3 ), and calculate the relative density of the structure.

[0222] (Linear transmittance)

[0223] The infrared transmission spectra of each test sample were obtained by using a FT-IR device using the transmission method. The results are shown in Figure 53 to Figure 55It should be noted that the linear transmittance of the infrared transmission spectrum is converted based on the Lambert-Beer law so as to be the linear transmittance at a thickness of 1 mm.

[0224] (Weight loss rate)

[0225] The weight loss rate of the structure is measured using a thermogravimetric analysis (TG) device. Specifically, 15 to 20 mg of the test sample is placed in an aluminum container, and heated from 30°C to 560°C at 10°C / min while passing dry air at 20 mL / min. Then, the first weight loss rate from 30°C to 200°C and the second weight loss rate from 200°C to 500°C are calculated. Specifically, the first weight loss rate from 30°C to 200°C is calculated by dividing the weight of the sample at 200°C by the weight of the sample at 30°C. Similarly, the second weight loss rate from 200°C to 500°C is calculated by dividing the weight of the sample at 500°C by the weight of the sample at 200°C. Their results are shown in Table 6. Fig.56 and Fig.57 .

[0226] Table 5

[0227]

[0228] Table 6

[0229]

[0230] like Fig.46 As shown in the figure, when the heat treatment temperature is 300℃~500℃, there is a heterogeneous phase (Na5Al3F 14 ). However, in any example, it was confirmed that the main phase was Na3AlF6 and the structure contained at least 95 mass % of Na3AlF6 polycrystal.

[0231] As shown in Table 5, the median value (d50) of the pore diameter of Examples 8 to 11 is 500 nm or less, which is very small. The porosity of Examples 8 to 11 is 30% or less. Fig.54 As shown in FIG. 1 , it was confirmed that the relative density of any structure was 70% or more, and that the structure was dense. From these results, it was confirmed that the structure was dense.

[0232] like Fig.53 As shown in Table 6, within the wavelength range of 3.8 to 5.7 μm (wavelength bandwidth 1.9 μm), the average linear transmittance per 1 mm thickness of the structure 1 of Examples 9 to 11 exceeds 60%. Fig.53 and Fig.55As shown in Table 6, it is found that the linear transmittance of the test samples of Examples 9 to 11 is higher than that of the test sample of Example 8 at a wavelength of about 4 μm, and the linear transmittance reaches the maximum when the heat treatment temperature is 400°C. Fig.56 and Fig.57 As shown, the second weight loss rate of Example 10 is less than 0.5%, which is less than half of that of Example 8. Fig.53 , Fig.56 and Fig.57 The results show that the amount of hydroxyl groups and water molecules in the structure is reduced by heat treatment, which inhibits infrared absorption and scattering caused by hydroxyl groups and water molecules and improves the transmittance of the structure.

[0233] (Note)

[0234] According to the description of the above embodiments, the following technology is disclosed.

[0235] (Technology 1) A structure comprising a base material of a continuous phase of a polycrystal of a composite fluoride, wherein the composite fluoride contains an alkali metal, the structure contains more than 85% by mass of an inorganic substance, the structure contains more than 50% by mass of a polycrystal of the composite fluoride, the porosity of the structure is less than 30%, the median value of the pore diameter of the structure is less than 500 nm, and the thickness of the structure is more than 10 μm.

[0236] According to this configuration, the structure is not easily dissolved in water and can be manufactured by a simple low-temperature process. Therefore, it is suitable for use in infrared transmission windows of gas sensors and flame detection sensors.

[0237] (Technique 2) The structure according to Technique 1, wherein the composite fluoride contains fluorine, the alkali metal, and at least one additional metal selected from the group consisting of alkaline earth metals, aluminum, gallium, indium, zinc, and yttrium as main components. Since the refractive index anisotropy of such composite fluoride is low, the transmittance of infrared light can be improved. Therefore, it is suitable for use in infrared transmission windows of gas sensors and flame detection sensors.

[0238] (Technique 3) The structure according to Technique 1 or 2, wherein the composite fluoride contains fluorine, the alkali metal and aluminum as main components. Since the refractive index anisotropy of the composite fluoride is low, the transmittance of infrared light can be improved. Therefore, it is suitable for use in infrared transmission windows of gas sensors and flame detection sensors.

[0239] (Technique 4) The structure according to any one of Techniques 1 to 3, wherein in the target wavelength band of 3 μm to 10 μm, the wavelength bandwidth in which the linear transmittance continuously exceeds 10% is 0.1 μm or more. According to this structure, infrared transmittance is improved. Therefore, it is suitable for use in infrared transmission windows of gas sensors and flame detection sensors, etc.

[0240] (Technique 5) The structure according to any one of Techniques 1 to 4, wherein in the target wavelength band of 3 μm to 5 μm, the wavelength bandwidth in which the linear transmittance continuously exceeds 50% is 0.1 μm or more. According to this configuration, the infrared transmittance is further improved. Therefore, it is further suitable for use in infrared transmission windows of gas sensors and flame detection sensors.

[0241] (Technique 6) A structure according to any one of Techniques 1 to 5, wherein the weight loss rate of the structure when heated from 200°C to 500°C is 0.5% or less. According to this configuration, the amount of hydroxyl groups and water molecules in the structure can be reduced, and infrared absorption and scattering caused by hydroxyl groups and water molecules can be suppressed. Therefore, infrared transmittance can be further improved.

[0242] (Technique 7) The structure according to any one of Techniques 1 to 6, which is an infrared transmission filter. According to this configuration, it is possible to provide an infrared detection device, a light emitting device, etc. that can suppress diffuse reflection of infrared light caused by pores.

[0243] (Technique 8) An infrared detection device includes the structure according to any one of Techniques 1 to 7. According to this configuration, it is possible to provide an infrared detection device capable of suppressing diffuse reflection of infrared light due to pores of the structure.

[0244] (Technique 9) A light emitting device comprising the structure according to any one of Techniques 1 to 7. According to this configuration, it is possible to provide a light emitting device capable of suppressing diffuse reflection of infrared light due to pores in the structure.

[0245] (Technique 10) A method for manufacturing a structure, comprising the steps of pressurizing and heating a raw material under the conditions of a pressure of 10 to 600 MPa and a temperature of 50 to 300° C., the raw material containing at least one of the following two: a first fluoride containing an alkali metal, a second fluoride containing a metal other than an alkali metal, and water; and a composite fluoride containing at least one of a hydroxyl group and a water molecule, wherein the structure contains more than 85% by mass of an inorganic substance, the structure contains more than 50% by mass of a polycrystal of the composite fluoride, the porosity of the structure is less than 30%, the median value of the pore diameter of the structure is less than 500 nm, and the thickness of the structure is more than 10 μm. Thus, the structure can be manufactured by a simple low-temperature process.

[0246] The entire contents of Tokugan Application No. 2022-114679 (filing date: July 19, 2022) are incorporated herein by reference.

[0247] As mentioned above, although this embodiment was demonstrated, this embodiment is not limited to these, Various deformation|transformation is possible within the range of the summary of this embodiment.

[0248] Industrial Applicability

[0249] According to the present disclosure, a structure suitable for use as an infrared transmission window of a gas sensor or a flame detection sensor, and an infrared detection device and a light emitting device using the structure can be provided. In addition, according to the present disclosure, a method for manufacturing the structure that can be manufactured by a simple low-temperature process can be provided.

[0250] Explanation of symbols

[0251] 1 Structure

[0252] 10 Basic Materials

[0253] 11 Continuous phase

[0254] 100 Infrared detection device

[0255] 200 Lighting Device

Claims

1. A structure comprising a base material comprising a continuous phase of a polycrystal of a composite fluoride, the composite fluoride comprising an alkali metal, The structure contains 85% by mass or more of inorganic substances, The structure contains 50% by mass or more of a polycrystal of the composite fluoride, The porosity of the structure is 30% or less, The median diameter of the pores of the structure is 500 nm or less, The thickness of the structure is 10 μm or more.

2. The structure according to claim 1, wherein The complex fluoride contains fluorine, the alkali metal, and at least one additional metal selected from the group consisting of alkaline earth metals, aluminum, gallium, indium, zinc, and yttrium as main components.

3. The structure according to claim 1 or 2, wherein: The composite fluoride contains fluorine, the alkali metal, and aluminum as main components. 4 . The structure according to claim 1 , wherein in a target wavelength band of 3 μm to 10 μm, a wavelength bandwidth in which the linear transmittance continuously exceeds 10% is 0.1 μm or more. 5 . The structure according to claim 1 , wherein in a target wavelength band of 3 μm to 5 μm, a wavelength bandwidth in which the linear transmittance continuously exceeds 50% is 0.1 μm or more.

6. The structure according to any one of claims 1 to 5, wherein: The weight loss rate of the structure when heated from 200° C. to 500° C. is 0.5% or less. 7 . The structure according to claim 1 , which is an infrared transmission filter. 8 . An infrared detection device comprising the structure according to claim 1 . 9 . A light emitting device comprising the structure according to claim 1 .

10. A method for producing a structure, comprising the steps of pressurizing and heating a raw material under the conditions of a pressure of 10 to 600 MPa and a temperature of 50 to 300° C., the raw material containing at least one of the following: a first fluoride containing an alkali metal, a second fluoride containing a metal other than the alkali metal, and water; and a composite fluoride containing at least one of a hydroxyl group and a water molecule, in, The structural body contains more than 85% by mass of inorganic substances, The structure contains 50% by mass or more of a polycrystal of the composite fluoride, The porosity of the structure is 30% or less, The median diameter of the pores of the structure is 500 nm or less, The thickness of the structure is 10 μm or more.

Citation Information

Patent Citations

  • Pour-out cap

    JP2022114679A

  • Method and device for analyzing gas

    WO2019176624A1